The local church and generational change in Birmingham, 1945-2000 - Jones, Ian (Boydell & Brewer, 2012)
The ongoing debate about secularisation and religious change in twentieth-century Britain has paid little attention to the experience of those who swam against the cultural tide and continued to attend church. This study, based on extensive original archive and oral history research, redresses this imbalance with an exploration of church-based Christianity in post-war Birmingham, examining how churchgoers interpreted and responded to the changes that they saw in family, congregation, neighbourhood and wider society. One important theme is the significance of age and generational identity to patterns of religiosity amidst profound change in attitudes to youth, age and parenting and growing evidence of a widening 'generation gap' in Christian belief and practice. In addition to offering a new and distinctive perspective on the changing religious identity of late twentieth-century English society, the book also provides a rare case-study in the significance of age and generation in the social and cultural history of modern Britain. Ian Jones is the Director of the Saltley Trust (an educational charity), Birmingham
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Geschichte 1900-2000; Geschichte; Kirchengeschichte; Church attendance / England / Birmingham / History / 20th century; Christians / England / Birmingham / Attitudes; Conflict of generations / England / Birmingham; Birmingham (England) / Church history / 20th century; Birmingham (England) / Religion / 20th century